Natural Gas Geochemistry in Jambanan Area, Sidoharjo, Sragen, Central Java, Indonesia - Dwi Yuda Wahyu Setya Pambudi; Amijaya, Hendra (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Natural gas was encountered on PAMSIMAS well drilling in the Jambanan area. Geochemical studies are needed to determine gas genesis in this area. Geochemical studies were carried out using the GC gas composition method on gas samples located at three locations, namely SRG-01, SRG-02, and SRG-03. The three gas samples had a methane content of 47.61 - 87.97mol.%. All three have a low wettability level (0.03-0.05%) which indicates that the gas is very dry. GC-IRMS Method was also used on SRG-01 and SRG-02 gas sample. Those gas samples have δ13C Methane characteristics of -40.7‰ (SRG-01) and -45.6‰ (SRG-02) with δD methane values ​​of -171‰ (SRG-01) and -178‰ (SRG-02). This shows that the gas at those are thermogenic gas and it comes from different levels of maturity, where the gas at SRG-01 is more mature than the gas at SRG-02.